2020
DOI: 10.1371/journal.pone.0243238
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and genetic diversity analyses of common bean germplasm collections of East and Southern Africa using morphological traits and high-density SNP markers

Abstract: Knowledge of genetic diversity in plant germplasm and the relationship between genetic factors and phenotypic expression is vital for crop improvement. This study's objectives were to understand the extent of genetic diversity and population structure in 60 common bean genotypes from East and Southern Africa. The common bean genotypes exhibited significant (p<0.05) levels of variability for traits such as days to flowering (DTF), days to maturity (DTM), number of pods per plant (NPP), number of seeds per po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 52 publications
4
25
0
Order By: Relevance
“…3) indicated that the landraces (P. vulgaris landraces and the two out-groups (P. coccineus and P. lunatus)) could be divided into two subpopulations with admixed landraces between the subpopulations. The results were similar to the population structure of P. vulgaris germplasm in Malawi, where delta K was the highest at K = 2 (Nkhata et al 2020). At the K = 3 levels, where the population was modelled to evaluate more genetic variations of the subpopulations and the admixtures, 38 landraces were grouped into two subpopulations based on the Bayesian genotype clustering approach.…”
Section: Genetic Relationships Among the Landracessupporting
confidence: 67%
See 3 more Smart Citations
“…3) indicated that the landraces (P. vulgaris landraces and the two out-groups (P. coccineus and P. lunatus)) could be divided into two subpopulations with admixed landraces between the subpopulations. The results were similar to the population structure of P. vulgaris germplasm in Malawi, where delta K was the highest at K = 2 (Nkhata et al 2020). At the K = 3 levels, where the population was modelled to evaluate more genetic variations of the subpopulations and the admixtures, 38 landraces were grouped into two subpopulations based on the Bayesian genotype clustering approach.…”
Section: Genetic Relationships Among the Landracessupporting
confidence: 67%
“…The lower heterozygosity values in the current study were probably caused by P. vulgaris as a naturally self-pollinating plant and most loci were probably homozygous (Nkhata et al 2020). The polymorphic information content (PIC) values show how beneficial specific markers are in diversification research (Nkhata et al 2020). The PIC that ranged from 0.00 to 0.58 among the P. vulgaris landraces in the current study (Table 4) was within a range from 0.00 to 0.96 recorded among the Brazilian landraces (Burle et al 2010).…”
Section: Genetic Diversity Among the Landracesmentioning
confidence: 50%
See 2 more Smart Citations
“…For common bean, DArTseq now provides an efficient and cost-effective strategy to generate SNPs for large-scale genome-wide studies [24]. For these analyses to be useful for future breeding programs, the results must be compared with the results of the morphological analyses to assist breeders in selecting source material [31].…”
Section: Introductionmentioning
confidence: 99%